Understanding the Olympics - Horne, John 1955-; Whannel, Garry (London Routledge, Taylor & Francis Group, 2016)
The Olympic Games is unquestionably the greatest sporting event in the world, with billions of viewers across the globe. How did the Olympics evolve into this multi-national phenomenon? How can the Olympics help us to understand the relationship between sport and society? What will be the impact and legacy of the 2016 Olympics in Rio? Now in a fully revised and updated new edition that places Rio 2016 in the foreground, this book answers all these questions by exploring the social, cultural, political, historical and economic context of the Games. This book presents the latest research on the Olympics, including new material on legacy, sustainability and corruption, and introduces the reader to all of the key themes of contemporary Olympic studies.
Part I : The contemporary Olympics. Breaking new ground : Rio 2016 -- London, the games and the legacies -- The IOC, political economy and the games bidding process -- Television and the commercialisation of the Olympic Games -- Urban development, city branding and the environment -- Part II : The history and politics of the Olympics. Reviving the Olympics -- From world's fairs to mega-events -- The internationalist spirit and national contestation -- Politics and the Olympics -- Festival, spectacle, carnival and consumption -- Part III : The future of the Olympics. Level playing fields -- The 'dark side' of the Olympics.
Includes bibliographical references and index.
Keywords: Olympics -- History; Olympics -- Social aspects